2021
DOI: 10.1155/2021/6626851
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antitumor Effect against Murine Cells of CT26 Colon Cancer and EL4 Lymphoma by Autologous Whole Tumor Dead Cells

Abstract: Active immunotherapy against cancer is based on immune system stimulation, triggering efficient and long-lasting antigen-specific immune responses. Immunization strategies using whole dead cells from tumor tissue, containing specific antigens inside, have become a promising approach, providing efficient lymphocyte activation through dendritic cells (DCs). In this work, we generate whole dead tumor cells from CT26, E.G7, and EL4 live tumor cells as antigen sources, which termed immunogenic cell bodies (ICBs), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The interplay of NO, HIF-1α, and lactate in IFN-γ-activated H6 cells reducing tumour growth led us to investigate the effects of these factors in non-NO-producing tumour cells with IFN-γ: CT26 and B16F10. These tumour cell lines are commonly injected into mice, subcutaneously or orthotopically, to establish tumour growth [50,51]. Our investigations revealed that CT26 cells basally express higher MHC class 1 and grow faster compared to B16F10 cells.…”
Section: Discussionmentioning
confidence: 72%
“…The interplay of NO, HIF-1α, and lactate in IFN-γ-activated H6 cells reducing tumour growth led us to investigate the effects of these factors in non-NO-producing tumour cells with IFN-γ: CT26 and B16F10. These tumour cell lines are commonly injected into mice, subcutaneously or orthotopically, to establish tumour growth [50,51]. Our investigations revealed that CT26 cells basally express higher MHC class 1 and grow faster compared to B16F10 cells.…”
Section: Discussionmentioning
confidence: 72%
“…The interplay of NO, HIF-1α, and lactate in IFN-γ-activated H6 cells reducing tumor growth led us to investigate the effects of these factors in non-NO-producing tumor cells with IFN-γ: CT26 and B16F10. These tumor cell lines are commonly injected into mice, subcutaneously or orthotopically, to establish tumor growth ( 50 , 51 ). Our investigations revealed that CT26 cells basally express higher MHC class 1 and grow faster compared to B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%